(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The article studies the educational significance of wisdoms with socio-spiritual content cited in the sources of world religions, compares them in terms of content, and provides methodological recommendations for teaching in the discipline of religious studies.